Biochemical and molecular insights into anthracnose resistance in chilli - Manisha Mangal; Jameel Akhtar; Arpita Srivastava; Pardeep Kumar; Sushma Sagar; Theivanai Murugan; Purva Khandelwal; Shilpi Kumari; Vinod Kumar Sharma; Jai Chand Rana (PLoS ONE, 2026)
Hot pepper ( Capsicum annuum L.) is a globally important vegetable crop valued for its nutritional, economic, and culinary significance, yet its productivity is severely threatened by the fruit-rot/anthracnose disease complex caused by Colletotrichum spp. ( C. capsici, C. gloeosporioides, and C. acutatum ). This study investigated the biochemical and molecular defense responses of two resistant genotypes, CH-281 (EC777200), resistant to C. capsici , and CH-319 (IC119695), resistant to C. gloeosporioides , in comparison with Kashi Anmol, which is susceptible to both pathogens. Resistant genotypes showed smaller lesion diameters, higher activities of antioxidant enzymes (SOD, CAT, GPX, POX), and increased phenolic accumulation, indicating effective oxidative stress management and sustained defense. Gene expression analyses revealed early and strong induction of defense-related genes in resistant lines. CH-281 challenged with C. capsici exhibited rapid upregulation of PR1 (996-fold), WRKY33, WRKY40, CaMYB, ACS, AOS, and Defensin-like proteins, whereas Kashi Anmol displayed delayed and weaker responses with late surges in ACS and AOS. Similarly, against C. gloeosporioides , CH-319 showed early activation of PR1, WRKY33, CaMYB, and Defensin-like proteins, while the susceptible genotype again demonstrated delayed induction with stronger late peaks. Overall, resistant genotypes mounted timely and robust biochemical and transcriptional defenses, in contrast to the susceptible genotype’s delayed responses. These findings highlight the molecular basis of anthracnose resistance and identify key defense genes and pathways that can be harnessed for breeding durable resistance in chilli.